Advancement of nanotechnologies in biogas production and contaminant removal: A review. (15th May 2023) - François, Mathurin; Lin, Kuen-Song; Rachmadona, Nova; Khoo, Kuan Shiong
Graphical abstract: Highlights: Recent progress of nanoparticles to remediate contaminants from wastewater. Strategies of nanotechnology in the production and purification of biogas. Advantage and limitation of nanoparticle performances are discussed. Performance of nanoparticles depends on various factors such as type of feedstock, dosage, pH and type of nanoparticles. Abstract: The challenges of managing fossil fuels, the continued emission of greenhouse gases into the atmosphere, and the global water crisis are increasingly drawing researchers' attention toward alternative ways to increase the efficiency of biogas production and wastewater treatment. To the best of our knowledge, no previous study has yet summarized the performance of nanomaterials in biogas production and the removal of waste contaminants from wastewater. Thus, this current review aims to describe the performance of nanomaterials in biogas production, wastewater treatment, and the removal of contaminants. Based on the identified research, the performance of nanoparticles (NPs) depends significantly on the dosage and feedstock used, the biodegradability of the feedstock, pH, and the type of nanoparticles. For the removal of contaminants, NPs have proved effective at removing CO2 and H2 S from biogas, as well as reducing the chemical oxygen demand (COD) and biological oxygen demand (BOD) of wastewater. Based on the evidence, NPs can improve biogas production and reduce contaminants in biogas and wastewater. The use of nanomaterials is recently an advance method over conventional approach for biogas production. The novelty of this study highlights that metal NPs, metal nutrient NPs, and iron oxide NPs are more suitable to increase biogas and CH4 production as compared to metal oxide NPs (e.g., CuO, Mn2 O3, Al2 O3, and ZnO). More research is needed to investigate the carbon footprint reductions in biogas production and wastewater treatment while accounting for various other parameters, including nanoparticle size and water temperature.